Choir Learning innovation through the vocalizing sadako Strategy - Habsari, Feby; Trisakti (Solah, 2025)
Non-academic education in senior high schools plays an important role in developing students’ talents and skills beyond academic aspects, one of which is through choir extracurricular activities. SMAMDA Voice, the choir group at SMA Muhammadiyah 2 Sidoarjo, is a platform for developing students’ interests and has achieved various national and international accomplishments. This success cannot be separated from the learning strategies applied, one of which is the Vocalizing Sadako strategy—an innovation by SMAMDA Voice’s coaches that combines physical and vocal warm-ups systematically. This study aims to describe the implementation of the Vocalizing Sadako strategy and its impact on improving students’ learning outcomes in choir practice. This research uses a descriptive qualitative approach with observation, interviews, and documentation techniques. The results show that the Vocalizing Sadako strategy can improve students’ vocal quality, discipline, and self-confidence in singing harmoniously. Through structured and consistent training, students show improvement in vocal technique, musicality, and teamwork in choir performances. In conclusion, the Vocalizing Sadako strategy is an effective learning innovation for improving students’ learning outcomes in choir extracurricular activities at SMA Muhammadiyah 2 Sidoarjo.